Profile of the Concept Understanding of Two-Dimensional Figure Based on Pirie Kieren's Theory Reviewed from Learning Motivation in Elementary School - Jannah, Ukhti Raudhatul; Amiruddin, Mohammad; Nurhidayati, Septia (FKIP Universitas Lampung, 2022)
This study aims describe understanding concept of two-dimensional figure based on Pirie Kieren’s theory in terms of learning motivation. This study uses a qualitative approach with a case study type of research. The results found that there were differences in the flow of students' understanding of high, medium, and low learning motivation in solving questions. When solving square questions, students with high learning motivation do effective folding back and arrive at inventing, students with motivation are doing infective folding back and not inventing, and students with low motivation do not fold back and do not get inventing. When solving rectangular problems, high-motivated students did ineffective folding back and did not arrive at inventing, moderately motivated students did not fold back and arrived at inventing, and low-motivated students did effective folding back and arrived at inventing. The similarity is that they both start from primitive knowledge. Keywords: concept understanding, Pirie Kieren Theory, two-dimensional figure. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1135-1148